Design of incentives in community based health insurance schemes - Rajeev Ahuja; Johannes Jütting (University of Bonn, Center for Development Research (ZEF), 2003)
Community based health insurance is an emerging and promising concept that has attracted the attention of policy makers as it addresses health care challenges faced by the poor. This paper discusses solutions to important incentive problems in micro-health insurance schemes which threaten their sustainability. In particular, three issues are explored: (i) if defining household as unit of insurance always mitigates adverse selection problem; (ii) how ex ante moral hazard problem can be circumvented through group insurance contract; and (iii) how to set incentives for scheme managers. Various public policies are discussed that help to set appropriate incentives to better manage health insurance schemes in low-income country environments.
Keywords: 330; Health Economics and Policy; Risk and Uncertainty; Gesetzliche Krankenversicherung; Gemeinde; Ökonomischer Anreiz; Adverse Selektion; Moral Hazard; Entwicklungsländer; Niedriglohnländer